Cripping inquiry: breathing life into co-produced disability methodologies - Julie Ellis; Louise Atkinson; Suzanne Glover; Jennifer Kettle; Grace Joseph; Jamie Hale; Amanda Jones; Mitch Coles; Libby Bligh; Ruth Bridgens; Conor O'Kane; Jenny Negus; et al. (Frontiers in Sociology)
IntroductionOur contributions within this article emerge from our experiences of co-leading a new Wellcome Discovery Award funded project, Cripping Breath: Towards a New Cultural Politics of Respiration. As a diverse team of clinicians, artists, academics and others with lived and embodied experience of disability, chronic illness, and neurodivergence, we are broadly exploring breathing and ventilation (e.g., forms of medical technology that support respiration) through arts-informed, archival, narrative and ethnographic research approaches.MethodsCripping Breath aims to forge new understandings of respiration from crip perspectives, which unapologetically center disability as a valued human experience. In this article, we unpack the meanings, politics and practices of crip perspectives and methodologies - forms of knowledge production that emerge from lived and embodied experiences of disability and chronic illness - and consider their contributions to our project so far. We think through crip time, Slow scholarship and (seemingly) radical things like rest and recuperation, and grief and loss within the research process.ResultsWe share the importance of embracing flexibility, adaptability and radical care as routine across our team, because we all bring various types of impairment, embodiment, chronic illness, and caring responsibilities.DiscussionWe question the meanings of these forms of welcoming in disability, impairment and difference as ways to develop radical and cripcultures of co-produced and innovative disability research methodologies, and conclude by calling for a more inclusive sociology.